Reliability of Trigonometric Transform-based Multi-Carrier Scheme - Mustafa, Samah A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
This work is looking for a new physical layer of a multi-carrier wireless communication system to be implemented in low complexity way, resorting to suitable fast transform. The work presents and assesses a scheme based on Discrete Trigonometric Transform with appending symmetric redundancy either in each or multiple consecutive transformed blocks. A receiver front-end filter is proposed to enforce whole symmetry in the channel impulse response, and bank of one tap filter per sub-carrier is applied as an equalizer in the transform domain. The behaviour of the transceiver is studied in the context of practical impairments like fading channel, carrier frequency offset and narrow band interference. Moreover, the performance is evaluated in contrast with the state of art methods by means of computer simulations, and it has been found that the new scheme improves robustness and reliability of communication signal, and record lower peak to average power ratio. The study demonstrates that front-end matched filter effectively performs frequency synchronization to compensate the carrier frequency offset in the received signal.